Basal contralateral aldosterone suppression is rare in lateralized primary aldosteronism. Issue 4 (October 2020) - Desrochers, Marie-Josée; St-Jean, Matthieu; El Ghorayeb, Nada; Bourdeau, Isabelle; So, Benny; Therasse, Éric; Kline, Gregory; Lacroix, André
Abstract : Context: : Unilateral aldosteronomas should suppress renin and contralateral aldosterone secretion. Complete aldosterone suppression in contralateral adrenal vein sample (AVS) could predict surgical outcomes. Objectives: : To retrospectively evaluate the prevalence of basal contralateral suppression using Aldosterone (A)contralateral(CL) /Aperipheral(P) as compared to (A/Cortisol(C)CL )/(A/C)P ratio in primary aldosteronism (PA) patients studied in two Canadian centers. To determine the best cut-off to predict clinical and biochemical surgical cure. To compare the accuracy of ACL /AP to the basal and post-ACTH lateralization index (LI) in predicting surgical cure. Methods: : In total, 330 patients with PA and successful AVS were included; 124 lateralizing patients underwent surgery. Clinical and biochemical cure at 3 and 12 months were evaluated using the PASO criteria. Results: : Using ACL /AP and (A/C)CL /(A/C)P at the cut-off of 1, the prevalence of contralateral suppression was 6 and 45%, respectively. Using ROC curves, the ACL /AP ratio is associated with clinical cure at 3 and 12 months and biochemical cure at 12 months. (A/C)CL /(A/C)P is associated with biochemical cure only. The cut-offs for ACL /AP offering the best sensitivity (Se) and specificity (Sp) for clinical and biochemical cures at 12 months are 2.15 (Se: 63% and Sp: 71%) and 6.15 (Se: 84% and Sp: 77%), respectively. Basal LI and post-ACTH LI are associated with clinical cure but only the post-ACTH LI is associated with biochemical cure. Conclusions: : In lateralized PA, basal contralateral suppression defined by ACL /AP is rare and incomplete compared to the (A/C)CL /(A/C)P ratio and is associated with clinical and biochemical postoperative outcome, but with modest accuracy.